Thymoxamine: lack of antihistaminic effects in clinical doses in man. - Al-Damluji, S; Grossman, A; Turner, P; Besser, G (1987)
The purpose of this study was to investigate whether the alpha 1-adrenoceptor antagonist thymoxamine possesses antihistaminic activity in clinical doses in man, as has been reported on the guinea pig ileum in vitro. Five normal subjects were given on three separate occasions intravenous infusions of thymoxamine (0.15 mg kg-1 loading dose followed by 0.15 mg kg-1 h-1), chlorpheniramine (1.5 mg loading dose followed by 1.5 mg h-1) and normal saline (placebo). Intravenous bolus doses of histamine (1 and 2 micrograms kg-1) were given after pretreatment with propranolol 10 mg to block the beta-adrenoceptor agonist effects of the catecholamines released by the histamine injections. Histamine caused a dose-dependent reduction of FEV1 and FVC that was antagonised by chlorpheniramine but not by thymoxamine, suggesting that thymoxamine has no antihistaminic activity in the doses used in man. Thymoxamine caused a small enhancement of the bronchoconstrictor effect of the lower dose of histamine. The relatively selective action of thymoxamine makes it a suitable agent for the investigation of alpha 1-adrenoceptors.